The Role of The Curator in Managing Bankrupt Assets in Relation to Actio Pauliana Lawsuits - Manik, Candoro Tua; Sunarmi, Sunarmi; Harianto, Dedi; Sukarja, Detania (LOCUS MEDIA PUBLISHING, 2024)
The management of bankrupt assets is entrusted to a curator appointed by the court and supervised by a supervising judge. The curator's duties include the management and settlement of bankrupt assets, including filing an Actio pauliana lawsuit for assets transferred before the bankruptcy ruling. The research questions include: 1) The compatibility of the curator's duties with Law Number 37 of 2004; 2) The evidence that can be presented by the curator; 3) The obstacles faced by the curator in presenting evidence. The research method employs a normative approach and field interviews. The findings indicate that curators encounter legal substance, structural, and cultural challenges, necessitating their active search for solutions to address issues in carrying out their responsibilities.